1991
DOI: 10.1016/0735-1097(91)90678-3
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-201 for assessment of myocardial viability: Quantitative comparison of 24-hour redistribution imaging with imaging after reinjection at rest

Abstract: Redistribution thallium-201 imaging 2 to 4 h after exercise may be incomplete and therefore may be inadequate to fully assess myocardial variability. Late redistribution imaging 24 h after exercise has been proposed to overcome this limitation of thallium stress imaging. However, because of poor count density the image quality on these studies is often suboptimal. In the present study the diagnostic information on 24-h planar thallium redistribution images was compared with that on images obtained after a rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This finding is consistent with previously published reports demonstrat ing a similar prevalence of Q waves among patients with normalized defects and those with fixed defects after rest 20IT1 reinjection [9], and the similar prevalence of Q waves in patients with reversible defects and those with fixed defects on late (24-hour) redistribution images stud ied by Yang et al [4], This finding is not unexpected since it is established that viability, reflected as regional FDG uptake, may be found in large myocardial regions associ ated with large Q waves [ 16. 17], Furthermore, Tillisch ct al.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with previously published reports demonstrat ing a similar prevalence of Q waves among patients with normalized defects and those with fixed defects after rest 20IT1 reinjection [9], and the similar prevalence of Q waves in patients with reversible defects and those with fixed defects on late (24-hour) redistribution images stud ied by Yang et al [4], This finding is not unexpected since it is established that viability, reflected as regional FDG uptake, may be found in large myocardial regions associ ated with large Q waves [ 16. 17], Furthermore, Tillisch ct al.…”
Section: Discussionsupporting
confidence: 82%
“…Rest thallium injection after 24-h planar imaging showed 50 new reversible segments among 126 segments without redistribution on 24-h imaging [18]. These two studies suggested the superiority of reinjection methods to 24-h imaging.…”
Section: Discussionmentioning
confidence: 64%
“…However, significant proportion of fixed defects can be considered viable. Several reports have revealed that additional late imaging or reinjection shows thallium redistribution or fill-in in the areas of fixed defects with conventional stress and delayed images [4,6,8,10,[17][18][19]. Positron emission tomography has been found to show metabolic activity in the zone of fixed thallium defects [10,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in patients showing apparently irreversible defects at 3-4 h, the identification of viable myocardium may be enhanced by the acquisition of a third set of images obtained 8-24 h later which allows for a longer period of Tl redistribution [2][3][4]. Furthermore, previous studies [5,6] showed that a quantitative analysis using planar imaging techniques after Tl rest-RI improved the detection of viability and predicted the recovery of left ventricular function of coronary bypass surgery. At times, it is important to complete a study as quickly as possible because this maximizes patient turnover, increases patient comfort, and expedites the decision-making process.…”
Section: Introductionmentioning
confidence: 99%